Effects of different calcium salts on the physicochemical properties of sliver carp myosin. (June 2022) - Hu, Yang; Zhang, Mengling; Zhao, Yu; Gao, Xia; You, Juan; Yin, Tao; Xiong, Shanbai; Liu, Ru
Abstract: To investigate the effects of different calcium salts on the physicochemical properties of myosin, the intermolecular interactions, particle size, surface hydrophobicity, reactive sulfhydryl group content and rheological properties of sliver carp myosin with the addition of four different kinds of calcium salts (CaCl2, calcium citrate (CC), nano-hydroxyapatite (HAP), tricalcium phosphate (TCP)) during gel processing were measured. The results showed that the addition of CaCl2 promoted the unwinding of α-helix, the increase in hydrophobic interactions, the formation of disulfide bonds of myosin, and increased the viscoelasticity of myosin. While, the addition of calcium citrate (CC) enhanced the hydrophobic interaction between myosin molecules, and the viscoelasticity of CC-added myosin was second only to the CaCl2 -added myosin. On the contrary, the addition of HAP and TCP interfered with the hydrophobic interaction between myosin molecules, and greatly reduced the viscoelasticity of myosin. In summary, calcium with high calcium release rate can improve the physicochemical properties of myosin, HAP and TCP with a very low calcium release rate interfered with the formation of myosin gelation. And it could be concluded that the calcium ions played a leading role in the physicochemical properties of myosin, the more calcium ion that the calcium salt can release, the better physicochemical properties the myosin were. Our work may provide an insight into the phenomenon why different kinds of calcium salts differ from each other on affecting the physicochemical properties of myosin during gel processing. Graphical abstract: Image 1 Highlights: - Calcium with high calcium release rate improve myosin's gelling properties - Ionized calcium plays a leading role in the gelling properties of myosin - CaCl2 promoted the unwinding of α-helix and increased the viscoelasticity of myosin